Fetal safety of nicotine replacement therapy in pregnancy: systematic review and meta‐analysis. (1st October 2020) - Taylor, Lauren; Claire, Ravinder; Campbell, Katarzyna; Coleman‐Haynes, Tom; Leonardi‐Bee, Jo; Chamberlain, Catherine; Berlin, Ivan; Davey, Mary‐Ann; Cooper, Sue; Coleman, Tim
Abstract: Background and aims: Smoking in pregnancy causes substantial avoidable harm to mothers and offspring; nicotine replacement therapy (NRT) may prevent this, and is used to help women to quit. A recently updated Cochrane Review of randomized controlled trials (RCTs) investigating impacts of NRT in pregnancy focuses primarily on efficacy data, but also reports adverse impacts from NRT. Here we identify and summarize NRT impacts on adverse pregnancy outcomes reported in non‐randomized controlled trials (non‐RCTs). Methods: Systematic reviews and meta‐analyses of RCTs and non‐RCT studies of NRT in pregnancy, with design‐specific risk of bias assessment and grading of recommendations, assessment, development and evaluations (GRADE) criteria applied to selected outcomes. Findings: Relevant Cochrane Review findings are reported alongside those from this new review. Seven RCTs were included; n  = 2340. Nine meta‐analyses were performed; non‐statistically significant estimates indicated potentially reduced risk from NRT compared with smoking for mean birth weight, low birth weight, preterm birth, intensive care admissions, neonatal death, congenital anomalies and caesarean section and potentially increased risks for miscarriage and stillbirth. GRADE assessment for mean birth weight and miscarriage outcomes indicated 'low' confidence in findings. Twenty‐three non‐RCTs were included; n  = 931 163. Eleven large studies from five routine health‐care cohorts reported clinical outcomes; 12 small studies investigated mainly physiological outcomes within in‐patient women given NRT. Findings from meta‐analyses for congenital anomalies, stillbirth and preterm birth were underpowered and not in a consistent direction; GRADE assessment of confidence in findings was 'very low'. Routine health‐care studies were of higher quality, but implications of reported findings were unclear as there was inadequate measurement and reporting of women's smoking. Conclusions: Available evidence from randomized controlled trials and non‐randomized comparative studies does not currently provide clear evidence as to whether maternal use of nicotine replacement therapy during pregnancy is harmful to the fetus.